Identification and quantification of anthocyanins in sorghum and sweetpotato leaves - Su, Xiaoyu (Kansas State University, 2018)
Anthocyanins are the most abundant water-soluble flavonoid pigments that are biosynthesized via the phenylpropanoid pathway in plants. Consumption of anthocyanin-rich vegetables and fruits has been linked with multiple health benefits in chronic disease prevention. This dissertation consisted of three studies as follows focused on the profiles and contents of anthocyanins in various sorghum accessions and sweetpotato leaves. Study 1: Sorghum is a rich source of various phytochemicals, but the contents of anthocyanins in various sorghum accessions are not clear. This study was to identify and quantify the anthocyanins by HPLC-DAD in selected 25 sorghum accessions with various phenotypic pericarp pigments. The predominant anthocyanins found in sorghums were 3-deoxyanthocyanidins including the unique leuteolinidin and apigeninidin analogs. The high levels of total anthocyanins were found in the red pericarp PI297139 and the brown pericarp PI221723, followed by the brown pericarp PI35038 and the yellow pericarp PI229838. There were moderate to low levels of anthocyanins observed in all the other accessions except for the white pericarp that generally contained least to undetectable amount. Although anthocyanins appeared to be associated with the pericarp color in the sorghum accessions with the highest contents in each pericarp pigment category, a distinguishable diversity of anthocyanin contents was presented among and between the phenotypic pericarp colors, suggesting other colorful phytochemicals such as carotenoids might be contributed. Establishing a database of anthocyanin profile and diversity in sorghum accessions with various pericarp pigments may lead to the development of novel functional sorghum products with active anthocyanin-enriched health benefits. Study 2: As phytochemical-enriched edible greens, sweetpotato (Ipomoea batatas L.) leaves have become popular. However, the profile and content of phytochemicals in sweetpotato leaves are mostly unknown. We previously bred a purple-fleshed sweetpotato P40 that demonstrated cancer prevention due to high levels of anthocyanins in the tuberous roots. The objectives of this study were to identify and quantify anthocyanins in P40 leaves when compared with the white-fleshed Bonita and orange-fleshed Beauregard. The mature leaves of P40 at 6-week vine stage were collected and extracted for anthocyanin analysis by HPLC-MS/MS. Fourteen anthocyanins, including a novel anthocyanin (peonidin 3-caffeoyl-p-coumaryl sophoroside-5-glucoside), were identified and quantitated. The contents of anthocyanins in P40 leaves (38 ± 2.9 mg/kg DW) were much lower than that in the tubers (13,100 ± 70 mg/kg DW). Furthermore, anthocyanin contents in P40 leaves were even lesser than those of the white-fleshed Bonita (448 ± 50.4 mg/kg DW) and orange-fleshed Beauregard (240 ± 60.9 mg/kg DW). Total phenolic contents as measured by Folin-Ciocalteu were 36.8 ± 4.8 mg GAE/g DW in the leaves of P40, but 46.7 ± 2.1 mg GAE/g DW in Bonita and 41.2 ± 5.0 mg GAE/g DW in Beauregard. No anthocyanin was detectable in the stems of these three sweetpotato varieties. Taken together, this study reports for the first time the profile and content of anthocyanins in the leaves of three sweetpotato varieties with a new anthocyanin identified. The unexpected lower levels of anthocyanins in the purple-fleshed sweetpotato leaves when compared with the tuberous roots advanced our existing database and also validated a diverse phenotype of anthocyanin biosynthesis between sweetpotato leaves and tubers. Study 3: As phytochemical-enriched edible greens, sweetpotato (Ipomoea batatas L.) leaves have potential health benefits. However, how anthocyanin content in sweetpotato leaves responds to harvest stages and growth conditions remains mostly unknown. In this study, we investigated the effect of harvest timing on the accumulation of anthocyanin in the leaves of several sweetpotato varieties: white-skinned and white-fleshed Bonita, red-skinned and orange-fleshed Beauregard, red-skinned and white-fleshed Murasaki, and purple-skinned and purple-fleshed P40. Anthocyanin content increased continuously in Bonita from 1st slip stage to vine stage, but P40 did not have the same response. Beauregard had most anthocyanin (592.5 ± 86.4 mg /kg DW) and total phenolic content (52.2 ± 3 mg GAE/g DW) of mature leaves at vine stage. The P40 variety had low anthocyanin and total phenolic content in the leaves although P40 tubers have the highest among these varieties. In the high tunnel studies, no significant differences in anthocyanin content were found in Beauregard leaves grown in the high tunnels versus the open field. Our study showed for the first time that anthocyanin levels were significantly affected by the growth stages. Our overall results indicate that growth stage and/or environmental factors among sweetpotato varieties affected anthocyanin content, which is highly variable and genotype-dependent. In conclusion, the three studies conducted in this dissertation provided a fundamental understanding of anthocyanin profiles and contents in various sorghum accessions with various phenotypic pericarp pigments and sweetpotato leaves in various growth stages and conditions. These results can be useful not only for the breeders but also consumers in the selection of sorghum accessions and sweetpotato varieties for anthocyanin-contained health benefits.
Keywords: Anthocyanin; Sorghum; Sweetpotato